New-onset diabetes as an emerging risk group for early detection of pancreatic cancer: current evidence, clinical challenge, and future directions - Tao, Lan Valerie; Karasinska, Joanna M.; Souza, Vanessa G. P.; Loree, Jonathan M.; Johnson, James D.; Renouf, Daniel J.; Schaeffer, David F. (Frontiers in Gastroenterology, 2026)
Pancreatic ductal adenocarcinoma (PDAC) is a deadly disease characterized by late-stage manifestation and relative resistance to standard therapies. Challenges with early detection and a paucity of effective therapies lead to one of the lowest 5-year survival rates among all cancers. Individuals around 50 years and over presenting with new onset diabetes (NOD) have a higher risk for PDAC diagnosis within 3 years of diabetes onset compared to the rest of the population. In this review, we contextualize NOD within other types of diabetes presentations such as type 1 diabetes (T1D), type 2 diabetes (T2D), and type 3 diabetes (T3cD), unravel the bidirectional relationship between diabetes and PDAC, and highlight potential biomarkers that may distinguish PDAC-associated diabetes from other predominant types of diabetes. Although practical applications of NOD currently fall short from being clinically actionable, clinical trials are underway to stratify NOD patients with PDAC-associated diabetes. Ultimately, these efforts could offer the rationale to implement early detection screening strategies to this subgroup of PDAC patients.